Efektivitas Model Pembelajaran Kooperatif Tipe Cooperative Integrated Reading and Composition (CIRC), Student Teams Achievement Division (STAD), Dan Jigsaw secara Online terhadap Hasil Belajar Siswa Kelas X Di SMK PGRI 1 Ngawi - Rohmatul; Erny Untari; Indra Puji Astuti (IAIN Kediri, 2021)
Research objectives 1) To find out whether there are significant differences in student learning outcomes who are subject to CIRC, STAD, and Jigsaw in class X at SMK PGRI 1 Ngawi; 2) to find out which one gives better student learning outcomes, students are subjected to CIRC, STAD, or Jigsaw. This study uses a quantitative approach with quasi-experimental research methods. The population is all students of class X at SMK PGRI 1 Ngawi for the Academic Year 2020/2021. The sample is 100 students. The sampling technique used is Simple Random Sampling. Data collection techniques using documentation and tests. The instrument test used validity, difficulty level reliability, and discriminatory power. Prerequisite tests are normality test and homogeneity test. The analysis technique used one-way ANOVA and further test with Scheffe test. Research results 1) There are significant differences in student learning outcomes who are subject to CIRC, STAD, and online Jigsaw in class X at SMK PGRI 1 Ngawi; 2) The learning outcomes of students who are subject to CIRC are better than the learning outcomes of students who are subject to STAD. The learning outcomes of students who were subjected to STAD were as good as the learning outcomes of students who were subjected to Jigsaw. The learning outcomes of students who were subjected to CIRC were as good as the learning outcomes of students who were subjected to Jigsaw.